Effect of fertility levels and bio-fertilizers on yield and economics of groundnut - Sharma, Sheela; Jat, N. L.; Shivran, A. C.; Choudhary, Shripal; Puniya, M. M.; Jeetarwal, R. L. (Annals of Agricultural Research, 2016)
A field experiment was conducted at S.K.N. College of Agriculture, Jobner (Rajasthan) during kharif 2011 on loamy sand soil to evaluate sixteen treatment combinations of four fertility levels (control, 50, 75 and 100% RDF) and four bio-fertilizers (control, Rhizobium, phosphate solubilizing bacteria and vesicular arbuscular mycorrhiza) on groundnut. Recommended dose of fertilizers (RDF) for groundnut was 20 kg N and 60 kg P2 O5 /ha. Results indicated that application of fertilizers up to 100% RDF recorded significantly higher number of pods per plant, kernels per pod, yields (pod, haulm and biological) and net returns (Rs. 51, 261/ha) over its preceding levels. However, seed index and shelling per cent were increased significantly only up to 75% RDF. Results further indicated that application of Rhizobium, being at par with PSB and VAM bio-fertilizers, significantly increased number of pods per plant, kernels per pod, seed index, pod, haulm and biological yields, shelling per cent over control, whereas net returns (Rs. 43, 717/ha) was significantly higher over control and VAM inoculation and remained at par to PSB inoculation.